Wear during quarrying : literature review :Powerpoint - Hack, H.R.G.K. (University of Twente, 2020)
This lecture presents: Wear during quarrying; Quarrying as old as humankind; Excavation methods; Excavation methods in quarries; Excavation & drilling mechanisms; Fire setting; Hydraulic/pneumatic hammer/breaker; Wear of excavators.